2016
DOI: 10.1007/s00701-016-2847-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of a three-dimensional endoscope for different skull base tumors: results of a preliminary extended endonasal surgical series

Abstract: In our experience, the 3-D endoscope represents a critical development in visualization, thus enabling improved hand-eye coordination and depth perception, which are mandatory for the management of complex intradural neurovascular structures during tumor removal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The subjective superiority of 3D endoscopy in EES has been widely reported by both clinical and laboratory studies and is confirmed by the subjective results of the present study . The present study showed significantly better rating of depth perception, discriminatory power and the value in performing delicate procedures using the 3D HD endoscope.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The subjective superiority of 3D endoscopy in EES has been widely reported by both clinical and laboratory studies and is confirmed by the subjective results of the present study . The present study showed significantly better rating of depth perception, discriminatory power and the value in performing delicate procedures using the 3D HD endoscope.…”
Section: Discussionsupporting
confidence: 88%
“…This endoscope has an interpupillary distance of 1.2 mm and a dynamic focus range of 8‐80 mm. It uses “insect eye” technology—incorporating an array of microlenses integrated into 4 mm optics—to project two separate endoscopic images onto dedicated sections of the camera chip . The images were displayed on a 24‐inch HD (1920 × 1080 pixels) stereoscopic LED flat screen that offered true stereoscopic images when passive polarising glasses were worn.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations